The Role of miRNA in Tumor Immune Escape and miRNA-Based Therapeutic Strategies - Zhang, Zhengjia; Huang, Qingcai; Yu, Liuchunyang; Zhu, Dongjie; Li, Yang; Xue, Zeyu; Hua, Zhenglai; Luo, Xinyi; Song, Zhiqian; Lu, Cheng; Zhao, Ting; Liu, Yuanyan (Frontiers in Immunology, 2022)
Tumor immune escape is a critical step in the malignant progression of tumors and one of the major barriers to immunotherapy, making immunotherapy the most promising therapeutic approach against tumors today. Tumor cells evade immune surveillance by altering the structure of their own, or by causing abnormal gene and protein expression, allowing for unrestricted development and invasion. These genetic or epigenetic changes have been linked to microRNAs (miRNAs), which are important determinants of post-transcriptional regulation. Tumor cells perform tumor immune escape by abnormally expressing related miRNAs, which reduce the killing effect of immune cells, disrupt the immune response, and disrupt apoptotic pathways. Consequently, there is a strong trend toward thoroughly investigating the role of miRNAs in tumor immune escape and utilizing them in tumor treatment. However, because of the properties of miRNAs, there is an urgent need for a safe, targeted and easily crossed biofilm vehicle to protect and deliver them in vivo, and exosomes, with their excellent biological properties, have successfully beaten traditional vehicles to provide strong support for miRNA therapy. This review summarizes the multiple roles of miRNAs in tumor immune escape and discusses their potential applications as an anti-tumor therapy. Also, this work proposes exosomes as a new opportunity for miRNA therapy, to provide novel ideas for the development of more effective tumor-fighting therapeutic approaches based on miRNAs.